Fatores associados à lentidão na velocidade de marcha em idosos da comunidade: estudo exploratório rede fibra - Ruggero, Cíntia Regina (2011)
Background: Gait speed has been considered a vital sign in older adults and is able to predict adverse health outcomes, such as falls and mortality. However, there are few studies about gait speed in Brazilian older population. We investigated the association between slower gait speeds (usual and fast gait speeds) and demographics, physical and mental health conditions, physical functioning performance and physical activity level. Methods: Cross-sectional, population-based study, including 385 community dwelling older adults, 65 years-old and more, men and women. Usual and fast gait speed (m/s) were obtained in a 4.6m pathway and the participants were classified in 3 groups through cluster analysis: slower - <0.91m/s; intermediate – 0.91 to 1.26m/s; faster- >1.26m/s to usual gait speed and slower l- <1.09m/s; intermediate – 1.09 to 1.57; faster - >1.57m/s to fast gait speed. Slower groups (SG) were compared to intermediate/faster groups (FG) regarding demographics, global cognitive function (Mini-Mental State Examination - MMSE), depression (Geriatric Depression Scale - GDS-15), concern about falling (Falls Efficacy Scale International - FES-I), subjective health perception, comorbidities, medications, visual and hearing impairments, memory and dizziness complain, self-perceived fatigue, disability in activities of daily living, height, body mass index and physical activity level. Results: Participants had 71.40(SD 5.72) years-old, 64.4% were female, the mean usual gait speed was 1.11 (SD 0.27) m/s and fast gait speed was 1.39 (SD 0.34) m/s. Slower usual gait speed was associated with low physical activity level, stroke, diabetes, arthritis, urinary incontinence (UI) and age while slower fast gait speed was associated with low physical activity level, UI, concern about falling, height and global cognitive function. Conclusion: Chronic conditions that affect mobility and low physical activity level seems to explain slower usual gait speed. Slower fast gait speed seems to be influenced by psico-cognitive variables and low level of physical activity. UI was associated to slower usual and fast gait speeds, suggesting that it is an important global marker of health status and functional reserve in aging.